Hemodynamic analysis of intracranial aneurysms using phase-contrast magnetic resonance imaging and computational fluid dynamics - Zhao, X.; Li, R.; Chen, Y.; Sia, S.F.; Li, D.; Zhang, Y.; Liu, A. (Springer Verlag (Germany), 2017)
Additional hemodynamic parameters are highly desirable in the clinical management of intracranial aneurysm rupture as static medical images cannot demonstrate the blood flow within aneurysms. There are two ways of obtaining the hemodynamic information—by phase-contrast magnetic resonance imaging (PCMRI) and computational fluid dynamics (CFD). In this paper, we compared PCMRI and CFD in the analysis of a stable patient’s specific aneurysm. The results showed that PCMRI and CFD are in good agreement with each other. An additional CFD study of two stable and two ruptured aneurysms revealed that ruptured aneurysms have a higher statistical average blood velocity, wall shear stress, and oscillatory shear index (OSI) within the aneurysm sac compared to those of stable aneurysms. Furthermore, for ruptured aneurysms, the OSI divides the positive and negative wall shear stress divergence at the aneurysm sac.